Absolute content determination by quantitative NMR (qNMR) spectroscopy: a curious case of aldosterone. Issue 38 (5th July 2021) - Singh, Neeraj; Taibon, Judith; Pongratz, Stephan; Geletneky, Christian
Abstract : 1D/2D-NMR based extensive analyses of the real structure of aldosterone, elucidating the plausible diastereomeric hemiacetal/hemiketal tautomers and a qNMR based method of absolute content determination. Abstract : Quantitative NMR spectroscopy has been utilized to calculate the absolute content (g g −1 ) of aldosterone, which is necessary for electrolyte balance and blood pressure regulation, in commercially available materials. Explanations have been provided for many signals observed in the 1 HNMR spectrum, false interpretation of which can have significant effects if such a value is utilized for the primary calibrators in ID-LC-MS/MS ('gold standard') reference methods in clinical chemistry.